Superficial temporal artery–middle cerebral artery bypass in combination with encephalo-myo-synangiosis in Chinese adult patients with moyamoya disease - Li, Lu; Wang, Anji; Wang, Changhui; Zhang, Hanbin; Wu, Deshen; Zhuang, Guangliang; Wang, Jie (Frontiers in Surgery, 2023)
Objective: To evaluate the feasibility and safety of superficial temporal artery (STA)–middle cerebral artery (MCA) anastomosis in combination with encephalo-myo-synangiosis (EMS) in Chinese adult patients with Moyamoya disease (MMD). Methods: A total of 65 patients with MMD who underwent combined STA–MCA bypass + EMS surgical revascularisation were included in this study. Each patient had a follow-up visit 6 months after discharge. Early bypass function was evaluated via computed tomography angiography and digital subtraction angiography, which were performed preoperatively and at 6 months after surgery. The perfusion parameters of cerebral blood flow (CBF), cerebral blood volume (CBV), mean transit time (MTT) and time to peak (TTP) were obtained and analysed. The clinical status of each patient was evaluated using a modified Rankin scale (mRS) preoperatively and at 1 week and 6 months after surgery. Results: Among the 65 enrolled patients, postoperative complications were observed in 5 (7.69%) patients, with 2 cases of dysphasia, 2 cases of new cerebral infarction and 1 case of seizure. Six months after surgery, 66 out of 68 hemispheres were found to have a functioning extra-intracranial bypass, and the patency rate was 97.06%. In terms of CBF perfusion, both the CBF and CBV increased significantly, while the MTT and TTP decreased after surgery. The mRS scores measured 1 week and 6 months after surgery were much lower than those measured preoperatively. Conclusion: A direct STA–MCA bypass procedure in combination with indirect EMS bypass is feasible and safe for Chinese adult patients with MMD.